Penguatan Kesadaran Hukum Masyarakat dalam Upaya Konservasi Penyu di Bajulmati Sea Turtle Conservation Kabupaten Malang - Sinda Eria Ayuni; Tikka Dessy Harsanti; Hibertus Sujiantoro; Galih Setyo Refangga (Abdimas Indonesian Journal, 2026)
Sea turtles are protected marine animals that still face serious threats due to hunting, egg harvesting, illegal trade, coastal pollution, and habitat destruction. Although legal protection has been regulated through various national instruments, the effectiveness of conservation still depends on public understanding and legal awareness. This community service activity aims to strengthen public legal awareness in supporting community based sea turtle conservation in Bajulmati Sea Turtle Conservation, Gajahrejo Village, Gedangan District, Malang Regency. The method used is a participatory and educational approach through partner coordination, field observation, directed interviews, focus group discussions, regulatory review, legal socialization, preparation of information media, and the release of baby turtles as an educational experience. The results of the activity showed that some residents and beach visitors did not fully understand the status of sea turtles as protected animals, the forms of prohibited actions, and the legal consequences of violations against turtles and their habitat. Legal socialization and direct involvement in the release of baby turtles were able to strengthen participants' understanding of the importance of protecting turtles not only as a legal obligation, but also as an ecological responsibility. This activity concluded that turtle conservation needs to be supported by ongoing legal education, easy-to-understand information media, clear reporting mechanisms, and collaboration between conservation managers, the government, related institutions, and the community.